GAMBARAN EPIDEMIOLOGI COVID-19 DI WILAYAH KABUPATEN KONAWE UTARA TAHUN 2020 - Irawati Irawati; Jafriati Jafriati; Lymbran Tina (Endemis Journal, 2022)
COVID-19 is an infectious disease that causes respiratory tract infections, such as flu, MERS (Middle East Respiratory Syndrome), and SARS (Severe Acute Respiratory Syndrome). North Konawe Regency is the 16th area in Southeast Sulawesi to find cases of COVID-19. The number of cases obtained was 45 cases in December 2020. The purpose of this study was to determine the epidemiological description of COVID-19 in the North Konawe Regency in 2020. This study was a descriptive study with a cross sectional design. This research was conducted through literature study and secondary data collection taken from the Health Service and BLUD of North Konawe District Hospital. The sampling technique used was themethod purposive sampling. The results showed that the most COVID-19 sufferers in the North Konawe Regency in 2020 were in the adult age category (26-45), namely 57.8%. The most dominant gender is female 60%. Most of the residential locations are the Kec. Asera 28.9%. Most of the care at home is 51.1%, the longest length of stay is 22 days with the category of length of stay classified as long (≤ 2 weeks) 57.8%. In the contact history, respondents did not have contact with positive COVID-19 patients 88.9%. In the history of comorbid people with a history of comorbidities of 62.2%. In travel history, respondents have never visited or lived in countries/regions or areas where COVID-19 is endemic in the last 14 days, 77.8%. Based on this research, it is hoped that the relevant agencies can carry out education to reduce the determinants of the incidence of COVID-19 to vulnerable groups so as to minimize the transmission of infection.